2018
DOI: 10.1039/c8ee00980e
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the performance and unexpected stability of partially coated water-splitting silicon photoanodes

Abstract: In spite of the notorious instability of Si in alkaline solutions, Si partially covered with hemispherical Ni particles show striking performances for sunlight-assisted water oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 63 publications
6
86
0
Order By: Relevance
“…BSi using an ALD-deposited TiO 2 protection layer. 22 In conclusion, we have reported a new strategy based on simple, low-cost wet methods to 13,14 is also effective on structured n-Si. We are confident that these results will inspire other groups to develop original designs for photoanodes that will be employed for cost-effective water splitting PECs.…”
Section: Acs Paragon Plus Environment Acs Applied Energy Materialsmentioning
confidence: 78%
See 1 more Smart Citation
“…BSi using an ALD-deposited TiO 2 protection layer. 22 In conclusion, we have reported a new strategy based on simple, low-cost wet methods to 13,14 is also effective on structured n-Si. We are confident that these results will inspire other groups to develop original designs for photoanodes that will be employed for cost-effective water splitting PECs.…”
Section: Acs Paragon Plus Environment Acs Applied Energy Materialsmentioning
confidence: 78%
“…Toward this goal, we first electroplated Ni 0 on the freshly-hydrogenated BSi using the same method as the one previously employed on planar Si. 13,14 This electrodeposition leads to the homogeneous decoration of the porous BSi layer with randomly-dispersed Ni nanoparticles (NPs). The role of these NPs role is to generate an array of robust nanoscale Schottky junctions, promoting an efficient hole transfer across the Si/Ni and Ni/electrolyte interface as well as a high photovoltage for sunlight-assisted OER, caused by the pinch-off effect.…”
mentioning
confidence: 99%
“…These results clearly indicated that the transformation of the nickel electrocatalyst follows different intrinsic routes in the absence/presence of illumination during water oxidation and exhibits a different electrochemical response under light illumination, especially regarding the splitting of the redox peaks. [38][39][40] To clarify the structural evolution that occurs during photoinduced water oxidation, we conducted real-time probing measurements using in situ X-ray scattering, which was developed to explicate the phase changes of an electrocatalyst during electrochemical water oxidation, to reveal the phase transformation that occurs during the (photo)electrochemical reaction. Figure S4 (Supporting Information) shows the transient photocurrent response of the n-Si@ Ni photoanode, in which the anodic wave corresponding to the oxidation of the nickel species was seen to occur before the OER onset potential.…”
Section: Resultsmentioning
confidence: 99%
“…[40,47] This reaction allowed the formation of Ni 0 atoms at the interface of Ni-Si in the presence of photogenerated holes caused by the illumination of Si. [40,47] This reaction allowed the formation of Ni 0 atoms at the interface of Ni-Si in the presence of photogenerated holes caused by the illumination of Si.…”
Section: Resultsmentioning
confidence: 99%
“…The nickel-iron catalyst is necessary for efficient charge injection into the electrolyte 28, [68][69][70][71] , and if it is not present, no oxidative current is obtained in the studied range of potentials (dotted line in Figure 3b). In fact, Ni(Fe)OOH is the real catalytic phase obtained after cycling in alkaline electrolytes such as standard KOH solutions, one of the earth-abundant OER catalyst with lower overpotentials 38,[72][73][74][75][76][77][78][79][80][81] In Figure 4, we present the topography and conductivity atomic force microscopy maps (c-AFM) of ALD-TiO2 samples grown on degenerately doped p + -Si substrates at 150 ºC and 300 ºC with 5 nm NiFe thermally evaporated on top. Measurements of TiO2/NiFe layers were performed at +1 V, simulating the electron flow from the tip to the substrate across the layer, like in OER anodic conditions.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%